2013
DOI: 10.1165/rcmb.2013-0022oc
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of LPS-Induced Lung Inflammation by Glucosamine in Rats

Abstract: Acute inflammation is often observed during acute lung injury (ALI) and acute respiratory distress syndrome. Glucosamine is known to act as an anti-inflammatory molecule. The effects of glucosamine on acute lung inflammation and its associated mechanisms remain unclear. The present study sought to address how glucosamine plays an anti-inflammatory role in acute lung inflammation in vivo and in vitro. Using the LPS intratracheal instillation-elicited rat lung inflammation model, we found that glucosamine attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…It has been reported that different expression patterns of the CINC family have been observed in various inflammation models. There was a high concentration of CINC-1 and CINC-2 in the airway of a rat model of chronic bronchopulmonary infection with Pseudomonas aeruginosa (Amano et al 2000 ), and Chuang et al reported that the protein and mRNA expression of CINC-1 was upregulated in an acute lung injury model induced by intratracheal LPS instillation (Chuang et al 2013 ). In the 1.0 mg-administered group in the present study, TiO 2 nanoparticles induced a transient expression of CINC in the rat lung after intratracheal instillation, but not in the 0.2 mg-administered group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that different expression patterns of the CINC family have been observed in various inflammation models. There was a high concentration of CINC-1 and CINC-2 in the airway of a rat model of chronic bronchopulmonary infection with Pseudomonas aeruginosa (Amano et al 2000 ), and Chuang et al reported that the protein and mRNA expression of CINC-1 was upregulated in an acute lung injury model induced by intratracheal LPS instillation (Chuang et al 2013 ). In the 1.0 mg-administered group in the present study, TiO 2 nanoparticles induced a transient expression of CINC in the rat lung after intratracheal instillation, but not in the 0.2 mg-administered group.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the current study have revealed a strong anti-inflammatory effect of GlcN in a sepsis model by attenuating pulmonary edema, neutrophil infiltration, nitrite production, and inflammatory cytokine production, as well as M1 polarization. GlcN is reported to attenuate LPS-induced lung inflammation in rats (30). The earlier study used intratracheal instillation of LPS to elicit local lung inflammation in rat and anti-inflammatory effects of GlcN in response to the cytokine mixture are examined using the rat alveolar cell line, L2.…”
Section: Protection Against Sepsis-induced Inflammation By Glucosaminementioning
confidence: 99%
“…IL-1β and TNF-α may serve as biomarkers of the NF-κB inflammatory pathway. A previous study using DXMS as a positive control determined levels of IL-1β and TNF-α to assess the protective effect of SFJDC in a rat model of LPS-induced ALI (26). Confocal laser scanning imaging revealed an obvious decrease in the levels of IL-1β in both rats treated with SFJDC and rats treated with DXMS compared to rats with untreated ALI.…”
Section: Discussionmentioning
confidence: 93%